Angle based Computer Vision Target locallization module for enhanced Military Surveillance - Radovanović Marko; Petrovski Aleksandar; Behlić Aner; Mustafovski Rexhep; Ilievski Kristijan; Jokić Željko; Ackovska Sofija (Scientific Technical Review)
This paper presents a novel system for accurately mapping military targets using a combination of trigonometry and computer vision, deployed through unmanned aerial vehicles (UAVs). The proposed system integrates a drone equipped with a camera and employes trigonometric principles to calculate target distances based on the drone's position, angles and elevation. Upon sighting a target, the system utilizes computer vision algorithms to precisely identify and localize it within the drone's field of view. Subsequently, leveraging the calculated distances and the drone's GPS coordinates, the system accurately maps the target's coordinates on a global positioning system (GPS). The integration of trigonometry and computer vision enhances target localization capabilities, facilitating efficient and precise mapping of military objectives in diverse operational environments. This system holds significant potential for enchancig situational awareness and operational effectiveness in military applications.